The Political Dimensions of Science Consciousness in Africa (Global Journal of Human-Social Science, 2020)
This paper explores the concept of science consciousness in the national life of African states. The publics in African states interact with new creations of science in the form of products imported from the developed countries, yet no one cares to communicate to these publics how such artefacts were arrived at -the science in simplified language behind such products as well as the intrigues (political, social, and even religious) that played out before such artifacts became reality. In this way, the general public in Africa does not flow with the science and politics of science behind the emergence of technological artefacts and new inventions which are sold to them as finished products. Each artifact of science tells a story that expands our science awareness and inspires the average mind. More rudimentarily, African governments have weak institutions that promote the knowledge of some science among the public or the masses and where private organizations which can perform this function exist the governments do not know what to do with them. In Africa today, science still exists only in the laboratory. For science to get into the cultures of African societies, it must first get into the everyday language of the people through whatever means.
Keywords: science consciousnes s; scientism; democratization of science; domestication of science; technologica